2022
DOI: 10.1002/jper.22-0254
|View full text |Cite
|
Sign up to set email alerts
|

Better living through chemistry? A randomized, double‐blind controlled study evaluating the efficacy of plaque control and gingival health impacts of a novel stannous fluoride‐containing gel

Abstract: Background: Gingivitis is a nonspecific inflammatory lesion in response to the accumulation of oral biofilm and is a necessary precursor to periodontitis.Enhanced oral hygiene practices are necessary to reverse gingivitis and a dentifrice that could provide significant clinical reductions in plaque accumulation and gingival inflammation would be desirable to treat gingivitis and potentially prevent progression to periodontitis. This clinical study aimed to investigate the effect of a novel stannous fluoride-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Previous studies have reported on the impact of the D1 dentifrice formulated without fluoride in patients with gingivitis and periodontitis. [20][21][22][23][24][25][26]31 These studies have demonstrated enhanced plaque reduction and improved gingival health in patients with gingivitis. 20,31 Additionally, when the D1 formulation without fluoride was utilized in Stage I/II periodontitis patients [32][33][34] investigators demonstrated increased reductions in periodontal probing depths, plaque, and gingival inflammation and bleeding when compared to control dentifrice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported on the impact of the D1 dentifrice formulated without fluoride in patients with gingivitis and periodontitis. [20][21][22][23][24][25][26]31 These studies have demonstrated enhanced plaque reduction and improved gingival health in patients with gingivitis. 20,31 Additionally, when the D1 formulation without fluoride was utilized in Stage I/II periodontitis patients [32][33][34] investigators demonstrated increased reductions in periodontal probing depths, plaque, and gingival inflammation and bleeding when compared to control dentifrice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on the impact of the D1 dentifrice formulated without fluoride in patients with gingivitis and periodontitis 20–26,31 . These studies have demonstrated enhanced plaque reduction and improved gingival health in patients with gingivitis 20,31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations